Corrigendum to the Review Article (Medit. Mar. Sci. 23/1 2022, 196-212): Established non-indigenous species increased by 40% in 11 years in the Mediterranean Sea - ZENETOS, ARGYRO; ALBANO, PAOLO; LÓPEZ GARCIA, EDUARDO; STERN, NIR; TSIAMIS, KONSTANTINOS; GALANIDI, MARIKA (Mediterranean Marine Science, 2022)
With this corrigendum, the authors of Zenetos et al. (2022) wish to notify readers of a small number of omissions and corrections in the updated inventory of Mediterranean non-indigenous species (NIS), recently undertaken by them, and amend the total number of NIS reported in the Mediterranean until December 2021.